Effects of Capsiate Supplementation on Maximal Voluntary Contraction in Healthy Men - dos Santos Gomes, Willemax; de Freitas, Marcelo Conrado; Dutra, Yago Medeiros; Rossi, Fabrício; Estanislau, Thiago Barros; Gonçalves, Daniela Caetano; Campos, Eduardo Zapaterra (International Journal of Sports Medicine, 2021)
This study aimed to investigate the effects of acute capsaicin analog (Capsiate - CAP) supplementation on maximal voluntary isometric contraction (MVIC) performance in healthy young men. Thirteen subjects (25.2±3.2 yrs) participated in the present study. In two different days separated by one week, the subjects ingested capsiate (12 mg) or placebo (starch: 12 mg) 45 minutes before a MVIC test. The MVIC test consisted of five 10-second knee extension maximal isometric contractions with 45 seconds of recovery between efforts. The peak force, mean force, minimum force, fatigue index, and area under the curve of each contraction were calculated. Main condition effect was found, with higher values of peak force (+4.83%, F=6.867, p=0.02), fatigue index (+8.96%, F=5.228, p=0.041), and area under the curve (+4.19%, F=4.774, p=0.04) for CAP compared to placebo, however, no interaction effect was found for any variable (F=0.090 to 1.356, p≥0.276). In summary, healthy young men produced higher maximal isometric force and delayed fatigue in the CAP condition compared to placebo condition (condition effect) but without significant difference between each effort.
Keywords: ergogenic effects; exercise tests; performance enhancing substances; nutrition